Policing in the Era of Increased Awareness of Wrongful Convictions: Police Officers' Reflections on Institutional Change, Public Pressures and the Nature of Modern Policing - Perry, Kanawha (2007)
The purpose of this research is to first establish an increase in the level of public awareness of wrongful convictions between 1996 and 2005. The second objective is to assess law enforcement officers' experiences in their jobs given the increased levels of awareness of wrongful convictions. Through interviews with North Carolina law enforcement officers, I analyze their experiences and examine how they perceive their jobs in light of changes that have come about in response to the increased awareness of wrongful convictions. The interviews reveal that officers are cognizant of the increased awareness of wrongful convictions and that they view law enforcement as the primary cause of wrongful convictions. Officers agree that although wrongful convictions have had a negative effect on the public's view of law enforcement, they have led to reforms and improvements in law enforcement strategies and techniques